Tongue Twisters in Pronunciation Class - Sitoresmi, Ulupi (Proceeding of International Conference on Teacher Training and Education, 2016)
To be able to speak English fluently or native-like for  foreign learners of this language  becomes their expectation to achieve. One of important elements that support successful communication using English is pronunciation. Without sufficient pronunciation skills, the learners may have limit ability to comunicate. The Indonesian language has different system from that of English including the sound system.Therefore, a teaching aid is needed to foster learners to improve their pronunciation skills.Tongue Twisters which consist of a combination of sounds that are hard for the mouth and tongue to manage especially for  non-native learners are meaningful tools to improve pronunciation. In this case, tongue twisters are implemented in pronunciation class of the second semester of English Department Faculty of Teacher Training and Education Slamet Riyadi University. The students reported that they had never used tongue twisters before. They found the drills useful and interesting. The class became fun and active. However, some still found difficulty while using tongue twisters especially the speed and time consuming. Tongue Twisters are useful drills to improve motivation, class condition, and pronunciation skill of the second semester students of English Department Faculty of Teacher Training and Education Slamet Riyadi University.